Alinhamento anatômico dos membros inferiores e lesões musculoesqueléticas em corredores: descrições, associações e taxas de lesão - Carvalho, Aline Carla Araújo (2011)
INTRODUCTION: There has been much speculation about the influence of factors such as upper limb alignment and the development of musculoskeletal injuries in runners; however, there is little evidence to support this hypothesis. Objectives: To describe the characteristics of lower limb alignment, to verify the prevalence and incidence of running-related musculoskeletal injuries, to analyze the associations between anatomical alignment and these injuries and to describe the main injuries among the runners and the most affected anatomical regions. Methods: This was a cross-sectional prospective cohort study with a twelve-week follow-up period including 89 recreational runners who were submitted to a bilateral evaluation of the Q angle, subtalar angle, plantar arch index and lower limb length discrepancy. Descriptive analyses were carried out as well as investigation of the association between the runners’ anatomical alignment and the injuries presented. The incidence of injuries was calculated using survival analysis, and the association between possible risk factors and the time of injury was determined with the Cox regression model. Results: Runners with a mean age of 44 (SD=10), without severe alterations in lower limb alignment and presenting an association between the discrepancy of Q angle and history of running-related musculoskeletal injuries in the last 12 months participated in the study. There was no association between the runners’ new injuries and lower limb alignment characteristics. The prevalence of musculoskeletal injuries from running was 61.8%, and their incidence was of 27%; the most common injuries were tendinopathies and muscle injuries, with the legs being the most affected region. Conclusions: an association between Q angle discrepancy and the runners’ injuries was identified; tendinopathies and muscle injuries were the main injuries, and the knee and leg were the most affected anatomical regions. KEYWORDS: Running, Sport Injuries, Physical Therapy, Physical Exercise.